Everything you need to know about hoarding - Drummond, Lynne M. (Cambridge University Press, 2025)
Are you or someone you know struggling with hoarding disorder, feeling ashamed or guilty about your belongings, and afraid to let them go? It's more common than you might think, affecting up to 6% of the general population. But despite its prevalence, seeking help can be challenging. This new book provides a clear description of hoarding, exploring it as a symptom of other issues as well as a condition in its own right. You'll learn about different treatment options and find step-by-step guidance and tools for recovery in the self-help section. Personal narratives and case studies make this guide accessible and relatable for those affected by hoarding, as well as their loved ones and health professionals. Don't let hoarding disorder control your life - take the first step towards recovery today with this invaluable resource.